Efficient catalytic conversion of corn stalk and xylose into furfural over sulfonated graphene in γ-valerolactone. Issue 19 (4th April 2019) - Ma, Jianru; Li, Wenzhi; Guan, Shengnan; Liu, Qiying; Li, Qingqing; Zhu, Chaofeng; Yang, Tao; Ogunbiyi, Ajibola Temitope; Ma, Longlong
Abstract : Catalytic conversion of corn stalk over sulfonated graphene. Abstract : Sulfonated graphene (SG) was prepared and employed to convert corn stalk and xylose into furfural. Transmission electron microscopy (TEM), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared spectroscopy (FT-IR) were used to characterize SG. The effects of reaction time, temperature, substrate loading, catalyst dosage and solvents on the reaction were researched and optimized. SG exhibited high catalytic activity in the conversion of xylose and corn stalk to furfural. A fairly high furfural yield of 96% was achieved at 150 °C from xylose and a 71.9% furfural yield was obtained when using a 10.7 ratio (mass ratio: xylose to SG) at 140 °C. While a 48% furfural yield was obtained from corn stalk (based on the starting combined moles of xylan and glucan in corn stalk; yield was >100%, if based on only xylan) using a substrate loading (corn stalk to catalyst mass ratio) of 2.14 and a 19% 5-hydroxymethylfurfural (5-HMF) yield was obtained. What's more, a 43.9% yield of furfural was obtained in only 20 min. In addition, the reusability of SG was also investigated and shown to have good stability for xylose dehydration.